Sources of resilience among UTM students with negative life events experiences - David, Dionietta, 1991-, author; Siti Rokiah Siwok, 1960-, supervisor; Fakulti Pengurusan (2014)
Project Paper (Sarjana Muda Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2014